Critical analysis on functional unit of Ain O Salish Kendra (ASK) - Islam, Md. Tamzidul (BRAC Univeristy, 2018)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Masters of Business Administration, 2017.